2019
DOI: 10.3748/wjg.v25.i32.4764
|View full text |Cite
|
Sign up to set email alerts
|

On-treatment monitoring of liver fibrosis with serum hepatitis B core-related antigen in chronic hepatitis B

Abstract: BACKGROUND Non-invasive evaluation for liver fibrosis is clinically important, especially in patients with undetectable hepatitis B virus (HBV) DNA treated with nucleoside analogs. AIM To clarify the monitoring power of hepatitis B core-related antigen (HBcrAg) for hepatic histologic changes in patients with chronic hepatitis B (CHB) treated with entecavir. METHODS This prospective multicenter study used multiple ordinal and multivariate logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
2
16
2
Order By: Relevance
“…Moreover, level of HBcAg can influence the progression of liver disease. 19 , 20 Our data showed that the proportion of positive HBcAg was significantly higher in patients with HBsAg+ HBV-GN, which is similar to liver injury of HBV infection. Moreover, our results showed that the levels of Scr, AST, ALT were much higher in HBsAg+ group when compared with HBsAg- group, which indicated HBsAg+ HBV-GN patients had poor kidney and liver function.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, level of HBcAg can influence the progression of liver disease. 19 , 20 Our data showed that the proportion of positive HBcAg was significantly higher in patients with HBsAg+ HBV-GN, which is similar to liver injury of HBV infection. Moreover, our results showed that the levels of Scr, AST, ALT were much higher in HBsAg+ group when compared with HBsAg- group, which indicated HBsAg+ HBV-GN patients had poor kidney and liver function.…”
Section: Discussionmentioning
confidence: 54%
“…The relationships between HBcrAg and histological changes differed among studies. [ 14 , 16 ] Chang et al [ 16 ] revealed that higher HBcrAg levels were associated with a higher grade of inflammation in all patients, and HBcrAg negatively correlated with liver fibrosis staging ( r = −0.357, P < 0.001) in HBeAg-positive patients but positively correlated ( r = 0.317, P < 0.001) in HBeAg-negative patients. They also found that a greater reduction in HBcrAg was associated with improvements in inflammation and regression of fibrosis when they analyzed 320 CHB patients (164 of whom were HBeAg-positive) who received 72 weeks of ETV.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that a greater reduction in HBcrAg was associated with improvements in inflammation and regression of fibrosis when they analyzed 320 CHB patients (164 of whom were HBeAg-positive) who received 72 weeks of ETV. [ 16 ] The study showed that there was a positive correlation between HBcrAg and the grade of inflammation and an inverse correlation between HBcrAg and the stage of fibrosis in HBeAg-positive patients but not in HBeAg-negative patients at baseline nor in all patients at 78 weeks. A decline in HBcrAg only correlated with improvements in inflammation in HBeAg-positive patients, not with the regression of fibrosis in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous clinical studies on the therapy of chronic hepatitis B, which tried to use HBcrAg instead of or in addition to HBV DNA for patient monitoring. A correlation of HBcrAg levels with the degree of liver fibrosis [35] and the development of hepatocellular carcinoma [36] was reported for HBeAg-negative patients. HBcrAg may be an acceptable substitute for HBV DNA for identification of patients requiring therapy [37], but monitoring of HBV DNA levels under antiviral therapy cannot adequately be done by HBcrAg in HBeAg-positive patients because nucleoside analogues do not suppress transcription of HBV DNA and the subsequent translation of HBeAg.…”
Section: Alternative Names For Hbv Antigens?mentioning
confidence: 92%